Screening for rearrangements in RB1/13q14 through real-time PCR - Freitas, Renata Mendes de (2018)
Fundação Oswaldo Cruz. Instituto de Tecnologia em Imunobiológicos (Bio-Manguinhos). Rio de Janeiro, RJ, Brasil.